Draft Seventh Five Year Plan 1985-1990 Government of Mizoram - Planning Commission (Planning Commission, 1985)
In the 7th Five Year Plan, the Forest Department will give emphasis on creating of Forest under plantation programmes, construction of roads and buildings, demarcation of existing forest areas and preservation of wildlife.
Forest Department, Government of Mizoram